Lesser Mealworm, Litter Beetle, Alphitobius diaperinus (Panzer) (Insecta: Coleoptera: Tenebrionidae) - James C. Dunford; Phillip E. Kaufman (EDIS, 2006)
EENY-367, a 12-page illustrated fact sheet by James C. Dunford and Philip E. Kaufman, provides information on the synonymy, distribution, description, life cycle and biology, damage, medical importance, and management of the lesser mealworm, Alphitobius diaperinus, which is a stored products pest and a vector for many poultry diseases. Includes 4 pages of bibliographic references. This publication was originally published on the Featured Creatures Web site by the UF Department of Entomology and Nematology, March 2006. Revised June 2006.